The Effect of Price, Sales Promotion and Product Quality on Purchase Interest in the Toyota Kijang Innova Zenix (Study on Toyota Hadji Kalla Branch Urip Sumoharjo - Achmad Taji (MANAGER: Journal of Management and Administration Science, 2023)
This study aims to find out and analyze the effect of Price, Sales Promotion, and Product Quality on Purchase Interests for the Toyota Kijang Innova Zenix vehicle at the Toyota Hadji Kalla Urip Sumoharjo Branch with a research time of 2 months starting from April to May 2013. The population in this study were all customers of Toyota Hadji Kalla Urip Sumoharjo Branch from January to April 2023 totaling 518 customers while the samples in this study were determined using the slovin formula so that the samples used in this study were 84 samples. This study used a survey method by distributing questionnaires. The results of the analysis show that Price has a negative and significant effect on Purchase Intention, Sales Promotion has a positive and significant effect on Purchase Intention, Product Quality has a significant positive effect on Purchase Intention, and simultaneously Price, Sales Promotion, and Product Quality have a positive and significant effect on Purchase Intention.